A regional trade model with Ricardian productivity gains and multi-technology electricity supply - Frank Pothen; Michael Hübler (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
This article presents an applied general equilibrium model which combines the theoretical foundations of an Eaton-Kortum type model of international trade with the complexity of a global multi-region, multi-sector Computable General Equilibrium (CGE) model of production and consumption. The Eaton-Kortum model features endogenous trade-induced productivity gains via Ricardian specialization and takes non-tariff trade costs into account. Model regions and sectors can be disaggregated, e.g., representing technology-specific electricity generation. The models is tailored to explicitly study the German Federal State of Lower Saxony, a prime location for renewable electricity generation in Germany with ambitious climate policy goals. The calibration utilizes the structural estimation of a gravity model with constraints, while the disaggregation adapts methods used in regional science and energy economics. With these features the model goes beyond standard CGE models and provides new insights in the nexus between trade policy and climate policy. Simulations suggest that the removal of tariffs creates smaller welfare gains than a comparable reduction of non-tariff barriers to trade but also a slightly smaller increase in global CO2 emissions. Trade policy-induced productivity gains and renewable energy subsidies significantly reduce carbon leakage from the EU to the rest of the world by making the EU more CO2-efficient. With its large wind power potential, Lower Saxony is less susceptible to negative effects of climate policy than the rest of Germany.
Keywords: C68; F10; F18; Q40; 330; international trade; regional model; climate policy; renewable energy; CGE